An acetylated derivative of vitexin halts MDA-MB-231 cellular progression and improves its immunogenic profile through tuning miR- 20a-MICA/B axis. Issue 18 (17th September 2021) - Awad, Aya R.; Youness, Rana A.; Ibrahim, M.; Motaal, Amira Abdel; El-Askary, Hesham I.; Assal, Reem.A.; Gad, Mohamed Z.
Abstract: The activating immune ligands, MICA/B, act as a "kill me" signal through the NKG2D receptor expressed on natural killer (NK) cells. Recently, the oncogenic miR-20a was found to mediate immune escape through repressing MICA/B levels in breast cancer (BC) cells. However, targeting miR-20a-MICA/B using natural compounds has rarely been investigated. Our group has successfully isolated 3'-O-acetylvitexin that showed cytotoxic effects against colon cancer cells but has never been evaluated in BC. Our aim is to investigate the effects of 3'-O-acetylvitexin on BC cell lines and to further elucidate its molecular mechanism of action.The results showed that 3'-O-acetylvitex depicted a more pronounced dose-dependent repression of TNBC cellular viability, colonogenicity and migration capacity than Vitexin. 3'-O-acetylvitexin treatment resulted in a marked dose-dependent repression of miR-20a with a concomitant dose-dependent increase in MICA/B expression. In conclusion, 3'-O-acetylvitexin might act as a promising therapeutic agent for TNBC patients. Graphical Abstract: